2020
DOI: 10.1002/micr.30648
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility study of preoperative microvessel evaluation and characterization in perforator flaps using various modes of color‐coded duplex sonography (CCDS)

Abstract: Background: Color-coded duplex sonography (CCDS) is useful for perforator flap design showing the highest sensitivity in identifying microvessels. This prospective study evaluates the feasibility of different ultrasound (US) modes applied by the microsurgeon in daily practice suggesting quantifiable reference values. Methods: Twenty-four patients aged between 17 and 68 years (mean 43.3 ± 14.2 years) with 18 anterolateral thigh (ALT) and 6 superficial circumflex iliac artery (SCIP) flaps were included. Indicati… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 37 publications
1
17
0
Order By: Relevance
“…In this context, reference values have already been provided for comparability in previous publications. 14 28 The present work not only described further adjusted device settings, but also how to precisely set US devices to make them applicable for the design of perforator flaps. It is supposed to address microsurgeons interested in learning CCDS perforator mapping by providing a structured methodology that simplifies preoperative markings and flap design to improve safety and efficiency.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this context, reference values have already been provided for comparability in previous publications. 14 28 The present work not only described further adjusted device settings, but also how to precisely set US devices to make them applicable for the design of perforator flaps. It is supposed to address microsurgeons interested in learning CCDS perforator mapping by providing a structured methodology that simplifies preoperative markings and flap design to improve safety and efficiency.…”
Section: Discussionmentioning
confidence: 99%
“…Exact machine settings for perforator imaging are of utmost significance for an efficacious execution and has been described by Kehrer et al previously. 13 14 Slow-flow detection as present in microvessels requires special US device trimming and may decisively enhance sensitivity for vessel detection and assessment. 15…”
Section: Discussionmentioning
confidence: 99%
“…While handheld Doppler has been shown to be less accurate than other modalities in localizing perforators, 2 duplex ultrasound has proved to be highly sensitive and accurate in perforator identification and characterization with the additional advantage of supplying information regarding flow characteristics. 102 A recent prospective study comparing duplex ultrasonography with handheld Doppler and CTA showed that color duplex was more sensitive, specific, and accurate than both other imaging modalities in identification of perforators as small as 0.5 mm, and there was 100% concordance between preoperative ultrasound data and intraoperative findings in 53 consecutive flaps. 9 While emerging modalities, such as DIRT and ICGA, have substantial promise, they are not yet widely available and their use is currently limited to specific applications.…”
Section: Discussionmentioning
confidence: 99%
“…Device calibration with adequate settings through our guide with just little practice should even enable beginners of CCDS and less-experienced microsurgeons to successfully achieve a level of expertise where what you see is what you get (intraoperatively). Further, micro-vessel characterization by determined by measuring quantitative parameters such as vascular diameter and blood flow velocities may possibly be useful for matching the flow velocity with the recipient vessels, e.g., if perforator-to-perforator anastomoses are used as described by Suh et al [ 2 ], it also allows for the comparison of values of SCIP micro-vessels with those of different (perforator) flaps [ 22 , 32 , 33 , 34 ]. Perforators of other flaps are usually also measured at their emergence point at the level of the deep fascia.…”
Section: Discussionmentioning
confidence: 99%